A Qualitative Case Study on Socio-Economic Deficiency and Causes of Illegal Fishing in the Riverine Biodiversity of Eastern Cape, South Africa. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Small-scale fishers in South Africa, particularly in the Western Cape, Eastern Cape, and KwaZulu-Natal, have historically faced exclusion from marine resource access and fishing rights. Despite policy reforms, Illegal, Unreported, and Unregulated (IUU) fishing continues to threaten their livelihoods and the sustainability of coastal ecosystems. This study assesses the socio-economic impacts of IUU fishing and evaluates the effectiveness of recent regulatory reforms aimed at addressing fisher marginalization. Methods A mixed-methods approach was adopted, combining semi-structured interviews with 83 small-scale fishers and 10 policymakers, and quantitative analysis of fishing rights allocation data and economic loss indicators. The study applied a poverty, vulnerability, and marginalization framework to assess both policy outcomes and lived community experiences. Results: Findings indicate moderate progress through initial rights allocation and stakeholder engagement. However, over 65% of fishers reported income loss due to IUU fishing, and 54% experienced declining food security. Despite new regulatory frameworks, 42% of eligible fishers remain excluded due to restrictive eligibility criteria, and 29% perceive the process as influenced by elite capture. Only 18% had access to alternative livelihoods. Enforcement remains inadequate, with 71% citing poor monitoring of IUU fishing, which continues to erode legal fishers’ efforts and ecosystem stability. Conclusion While current reforms are a step forward, weak enforcement, exclusionary rights allocation, and limited livelihood alternatives undermine their effectiveness. These challenges reduce the resilience of small-scale fisheries and threaten long-term sustainability. Recommendations To improve outcomes, enforcement of IUU fishing regulations must be strengthened, eligibility criteria broadened, and targeted support provided for alternative livelihoods. A more inclusive, community-driven approach is essential for sustainable fisheries governance in South Africa.